2003
DOI: 10.1016/s0006-3495(03)74471-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Implications of the Instability of the ADP/ATP Transporter Purified from Mitochondria as Revealed by FTIR Spectroscopy

Abstract: The ADP/ATP transporter shows a high instability when solubilized, making it difficult to obtain functional protein with sufficient purity for long-term spectroscopic studies. When solubilized in the detergent dodecyl maltoside the protein is in equilibrium between the so-called CATR and BA conformations and in a few hours it becomes nonfunctional, unable to bind either its inhibitors or its substrates. By Fourier transform infrared spectroscopy, we studied the structural changes involved in this denaturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Because of this experimental difficulty, it has been much less studied than the amide I and amide II vibrations. For membrane proteins adopting a helical structure the amide A is centered at around 3300 cm –1 ,, and for β-sheets at ∼3250 cm –1 . , Because of the cancellation of the bulk water absorption, amide A vibrations are often resolved in IR difference spectra ,, but rarely used to derive structural information because of the lack of detailed theoretical and experimental studies to interpret the observed changes.…”
Section: Integration and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this experimental difficulty, it has been much less studied than the amide I and amide II vibrations. For membrane proteins adopting a helical structure the amide A is centered at around 3300 cm –1 ,, and for β-sheets at ∼3250 cm –1 . , Because of the cancellation of the bulk water absorption, amide A vibrations are often resolved in IR difference spectra ,, but rarely used to derive structural information because of the lack of detailed theoretical and experimental studies to interpret the observed changes.…”
Section: Integration and Interpretationmentioning
confidence: 99%
“…For instance, it is particularly difficult to control the final ionic strength in the sample, which can be an important parameter (a) Absorption spectrum of the detergent solubilized mitochondrial ATP/ADP carrier at 8 mg/mL in a H 2 O buffer, overlaid with the scaled spectrum of the buffer. 117 The subtraction of the sample and the scaled buffer spectra reveals the absorption from the protein (and detergent). The amide I−II region of the protein is expanded for a better visualization, showing a maximum absorbance of 0.02.…”
Section: 2)mentioning
confidence: 99%
“…8C). Based on their frequencies, they can be tentatively assigned to the submicrosecond elongation of β-hairpins [1,640-1,625 cm −1 (35)] from extramembrane loops [∼1,662 cm −1 (38)]. However, the negative absorption at 1,663 cm −1 may also comprise changes in the νC=N of the protonated SB, the frequency of which has been assigned to 1,657 cm −1 by resonance Raman spectroscopy (18).…”
Section: Structural Changes Of the Protein Backbonementioning
confidence: 99%
“…Other times, positive and negatives values should be expected in a deconvoluted spectra for physical reasons, as for infrared lineal dichroism spectra [51][52][53] or for difference spectra. For instance, several papers have reported infrared difference spectra corresponding mainly to protein conformational changes upon substrate binding.…”
Section: Introductionmentioning
confidence: 99%